Pullulan-based nanoparticles as carriers for transmucosal protein delivery - Dionísio, Marita (2013)
Polymeric nanoparticles have revealed very effective in transmucosal delivery of proteins. Polysaccharides are among the most used materials for the production of these carriers, owing to their structural flexibility and propensity to evidence biocompatibility and biodegradability. In parallel, there is a preference for the use of mild methods for their production, in order to prevent protein degradation, ensure lower costs and easier procedures that enable scaling up. In this work we propose the production of pullulan-based nanoparticles by a mild method of polyelectrolyte complexation. As pullulan is a neutral polysaccharide, sulfated and aminated derivatives of the polymer were synthesized to provide pullulan with a charge. These derivatives were then complexed with chitosan and carrageenan, respectively, to produce the nanocarriers. Positively charged nanoparticles of 180-270 nm were obtained, evidencing ability to associate bovine serum albumin, which was selected as model protein. In PBS pH 7.4, pullulan-based nanoparticles were found to have a burst release of 30% of the protein, which maintained up to 24h. Nanoparticle size and zeta potential were preserved upon freeze-drying in the presence of appropriate cryoprotectants. A factorial design was approached to assess the cytotoxicity of raw materials and nanoparticles by the metabolic test MTT. Nanoparticles demonstrated to not cause overt toxicity in a respiratory cell model (Calu-3). Pullulan has, thus, demonstrated to hold potential for the production of nanoparticles with an application in protein delivery.